SOCIOECONOMIC STATUS AND PHYSICAL ACTIVITY DURING ELEMENTARY SCHOOL STUDENT RECESS - zuñiga, uriel (2021)
Introduction: The association between socioeconomic status (SES) and the level of physical activity (PA) at school has not been studied at length. Objective: To describe the association between SES and the intensity of physical ac tivity during recess in elementary school children as well as the space dedicated to physical activity. Methods: A total of 212 children (110 boys and 102 girls) who were enrolled in the fourth, fifth and sixth grade of elementary school at the time participated in this study. The subjects were divided into 4 levels according to the marginalization index (MI). The geographical location of the schools and the available area were calculated using Google Maps Pro (GMP) software.1 Physical activity level was measured using accelerometry.2 Comparisons of different levels of PA with respect to marginalization indices and sex were investigated using one-way analysis of variance. The association between health variables and PA was determined through the Pearson correlation coefficient. Results: Results indicated that the level and intensity of PA during recess are associated with socioeconomic status and the social marginalization index, as well as sex, age, and infrastructure. Conclusion: The higher the level of social marginalization, the lower the level of PA and the smaller the space dedicated to PA.